Early sST2 Liberation after Implantation of a Left Ventricular Assist Device in Patients with Advanced Heart Failure. (28th December 2020) - Opfermann, Philipp; Simader, Elisabeth; Felli, Alessia; Bevilacqua, Michele; Holaubek, Caroline; Dworschak, Martin; Mouhieddine, Mohamed; Zimpfer, Daniel; Ankersmit, Jan Hendrik; Steinlechner, Barbara
Abstract : Background . The use of left ventricular assist device (LVAD) has increased considerably over the past decade; however, there is limited literature to assist in patient selection and monitoring. The frequency of adverse events remains high. We examined the early expression of circulating soluble ST2 (sST2), a biomarker with immunosuppressive and profibrotic activity, and assessed the risk of death at 1 year in patients receiving LVAD implant. Methods . We prospectively enrolled 20 heart failure patients and measured sST2, IL-33, and IL-6 serum concentrations over three weeks after LVAD implantation. We compared the kinetics of IL-6, sST2, and IL-33 release in survivors with those of nonsurvivors using mixed model two-way analysis of variance for repeated measures. We also collected data on hemodynamic parameters (i.e., cardiac output) and frequency of infections during the hospital stay. Results . LVAD therapy led to an immediate and significant improvement of the hemodynamic parameters in 1-year survivors and nonsurvivors alike. The 1-year survival rate was 65%. IL-6 concentrations showed a significant (p = 0.03 ) peak at admission to the intensive care unit following LVAD implantation, whereas sST2 levels were massively increased (p < 0.0003 ) on day 1. While 1-year survivors had persistently lower sST2 values compared to nonsurvivors during the first 3 weeks after LVAD implantation (p = 0.012 ), no differences were observed in the temporal pattern of IL-6 or IL-33. The odds of detecting Candida species in the bronchoalveolar lavage fluid were 14 times higher in nonsurvivors than in survivors (OR 13.7, CI 1.4-127, p = 0.02 ). Conclusion . In patients implanted with LVAD, circulating sST2 levels and frequency of Candida colonisation were associated with higher mortality. Awareness of this early immune response can guide physicians in risk-benefit analysis.